Pengaruh Waktu Tanam dan Genotipe Padi Gogo terhadap Hasil - D.H., Totok A.; Suwarto, Suwarto; Riyanto, A.; Susanti, D.; Kantun, I. N.; Suwarno, Suwarno (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Upland rice plays an important role in supporting food security for community in dryland areas. Genotype Ã environment interaction is an important factor to be considered in the development of upland rice in Indonesia, because they affect rice yield stability. Genotype Ã environment interaction and yield stability of rice genotypes are important information to be considered for the development of upland rice. The study was conducted over two years on a dry land area of Banjarnegara, Central Java, using 10 genotypes of upland rice (UNRAM 1E, 4E UNRAM, UNRAM 17E, 9E UNRAM, Unsoed G10, G19 Unsoed, Unsoed G39, G136 Unsoed, B12644F-MR-2, B12498C-MR-1) and two varieties (Situ Patenggang and Way Rarem) as control. Data were analyzed using analysis of variance. Results showed that planting time affect yield and yield components of the upland rice tested. Effect of the genotype x planting time interaction was shown on plant height, flowering date, harvest age, and crop yields. The upland rice genotypes that showed a stable high yields over years of planting were UNRAM 4, Unsoed G10, G136 Unsoed, B12644F-MR-2, and Situ Patenggang and Way Rarem.